Production of semi- refined carrageenan from Eucheuma cotonii. - Mustapha, Saari; Zainal Abidin, Zurina; Chandar, Haris; Sahgravani, Reza; Harun, M. Y. (2011)
This study presents alkaline extraction of red seaweed, Eucheuma cotonii, to yield semi-refined carrageenan (SRC) of kappa type. Temperatures 60-80°C were suitable for extraction of SRC. At 80°C using 1.0 M KOH, produced SRC contained the highest purity of 3, 6-anhydrogalactose, a lower heavy metal concentration and gave highest rupture force.